Occupational history of exposure to zoonotic agents in people dedicated to livestock in San Pedro de los Milagros, Antioquia, Colombia (2019)
ABSTRACT : Introduction: According to the World Health Organization, livestock farming is one of the anthropic activities in which workers are exposed to various zoonotic agents. Objectives: To establish the frequency of seropositivity (IgG antibodies) against some zoonotic agents in people with occupational exposure to livestock in San Pedro de los Milagros (Antioquia), and to analyze associated factors. Materials and methods: Descriptive study carried out on a population of 328 cattle farmers. Demographic data were collected and the seropositivity frequency of IgG antibodies to Babesia bovis, Babesia bigemina, Anaplasma phagocytophilum, Ehrlichia chaffensis, Borrelia burgdorferi, Coxiella burnetii, Francisella tularensis, Brucella abortus, Brucella suis, Leptospira interrogans, and Toxoplasma gondii was determined. Overall and specific prevalence, prevalence ratios and binary logistic regressions were estimated. Results: The highest seropositivity frequencies were 47.6% for T. gondii, 33.5% for B. burgdorferi and 13% for E. chaffensis. The prevalence of T. gondii and B. burgdorferi had statistical association with sex [RP:1.3 (CI:1.0-1.8) and 2.0 (CI:1.1-3.9) respectively], and age group [(RP:1.5 (CI:1.2-1,9) and 2.5 (CI:1.4-6.4) respectively]. In workers with more than 10 years of related work experience, statistical association was 50% [RP:1.5 (CI:1.2-1.9) and 2.5 (CI:1.6- 2.3), respectively]. There were no seropositive results for B. abortus, B. suis, B. bovis and B. bigemina. Conclusions: Exposure to some zoonotic agents was evidenced. This is determinant for the knowledge of tropical zoonotic diseases transmitted by vectors in livestock production systems.